Neoliberal restructuring, disabled people and social (in)security in Australia and Britain - Grover, C.; Soldatic, Karen (2013)
This paper examines recent social security policies in Australia and the UK for workless disabled people. The paper outlines developments in both countries over the past two decades and points to the fact that while there may be differences in the detail, the trends in such policies in the two countries are similar. This involves moves towards stricter eligibility criteria, greater expectation of workless disabled people to make efforts to (re)enter paid employment and, through such processes, a redrawing of the 'disability category' that denotes the 'truly' disabled from those who are deemed capable of doing at least some paid work. The paper goes on to consider explanations of such change, arguing that liberal explanations in the social administration tradition are problematic and that they, therefore, need to be placed within the neoliberal project, in particular its concern with putting people to work. The paper concludes that this has essentially involved a redrawing of the disability category to ensure a smaller number of people of working age in both countries can legitimately claim an existence outside of paid work. The paper also argues that more comparative research is required to understand the impacts of such trends on disabled people and provide insights for those resisting the influence of neoliberalism on welfare regimes.